The prognostic value of lymphocyte-to-monocyte ratio in retinopathy of prematurity - Yu-Xiang Hu; Xiao-Xuan Xu; Yi Shao; Gao-Le Yuan; Feng Mei; Quan Zhou; Yi Cheng; Jun Wang; Xiao-Rong Wu (International Journal of Ophthalmology, 2017)
AIM: To evaluate the associations between development of retinopathy of prematurity (ROP) and serum lymphocyte-to-monocyte ratio (LMR), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR). METHODS: A retrospective cohort study was performed, involving infants who were screened for ROP from January 2015 to December 2015. Preterm newborns of ≤32 gestational weeks with ROP were enrolled as the observation group, and non-ROP infants were enrolled as the control group, whose complete blood cell were measured within the first 24h of life. The levels of NLR, LMR and PLR were determined in all groups. The data obtained were analyzed using univariate and multivariate logistic regression analysis. RESULTS: In this study, 40 cases of ROP were enrolled and 40 cases of non-ROP as controls. The LMR levels were significantly higher (P<0.001) in ROP group (3.96±1.16) compared to non-ROP group (2.85±0.79). The NLR levels were significantly lower (P=0.035) in ROP group {median [interquartile range (IQR)], 0.88 (0.67-1.46)} compared to non-ROP group [median (IQR), 1.20 (0.85-1.89)]. The median PLR values were 61.99 (IQR, 50.23-75.98) in ROP group and 69.24 (IQR, 55.52-88.12) in non-ROP group (P=0.104). Logistic regression analysis suggested that LMR was an independent risk factor for ROP (OR: 0.275; 95% CI: 0.134-0.564; P=0.001). CONCLUSION: The findings demonstrate that higher LMR is independently and significantly associated with the development of ROP, and the LMR may be invoked as a predictive tool for identifying risk for ROP.